"I Want to Have the American Dream": Messages of Materialism as a Driving Force in Juvenile Recidivism. (May 2019) - VanderPyl, Taryn
Youth in the United States are raised with the message that economic achievement and the American Dream are the only means to obtain true success and happiness. Those youth who face barriers to these standards of achievement, however, internalize any shortcomings as their own personal failure, heightening the appeal of criminal means of monetary gain. Scholars have explored the correlation between materialism and youth crime, but have done so without involving youth in research about themselves. In this study, a content analysis was conducted of 1, 008 writing samples from incarcerated youth in an effort to prioritize youth voice and perspective. Messages of materialism and its deleterious effects frequently emerged as prominent concerns for these youths. Incarcerated youth are missing interventions to devitalize materialism's function as a motivating or justifying factor in criminal or delinquent acts, thus contributing to reoffending when they fail to achieve their economic goals through legal means.